A Comparison of Four Stream Substratum Restoration Techniques Concerning Interstitial Conditions and Downstream Effects. (13th January 2014) - Pander, J.; Mueller, M.; Geist, J.
Abstract Stream substratum plays a key role for many riverine species and has become a focus topic in the context of structural habitat improvements. There is a lack of studies that compare the effectiveness of different substratum restoration measures. Herein, we compare four restoration techniques (two different gravel introductions, substratum raking and sickle‐formed constrictor) that were carried out in six replicate rivers. Each measure was monitored for changes in physicochemical substratum quality and the effects of the construction work on downstream sites. Generally, the effects on physicochemical substratum quality were highly variable between restoration types and rivers and strongly decreased within 1 year. Most pronounced changes of substratum quality were detected for the gravel introductions. Substratum raking and the sickle‐formed constrictor had the smallest effects, which were dependent on the original substratum composition of the restored sites. At the same time, substratum raking caused an average fine sediment deposition of 17 kg m−2 on downstream sites, being sixfold higher than for the other measures. Consequently, all of the investigated substratum restoration techniques are confined to short‐term improvement of substratum quality. This finding, together with the observed damage on downstream sites, suggests that a rethinking of the currently applied restoration techniques is required, better considering catchment and natural substratum dynamics in river restoration. Copyright © 2014 John Wiley & Sons, Ltd.